Photochemical bonding of special optical fibers - Ertman, Slawomir; Bielska, Monika; Czapla, Aleksandra; Domosławski, Krzysztof; Chychłowski, Miłosz; Reszka, Karolina; Woliński, Tomasz R. (Photonics Letters of Poland, 2014)
The most popular method for permanent connecting of an optical fibers is a thermal bonding with a fusion or filament splicers. However this method in some cases is not suitable, for example if connected fibers are made of materials with different melting temperatures (i.e. silica and “soft glass fibers) or in the case of microstructured optical fibers filled with materials, which are highly sensitive for high temperature (i.e. organic materials such a liquid crystals). In this work we will present some practical issues of an alternative method of permanent connecting of various types of optical fibers by gluing with use of photo-curable adhesives. Full Text: PDF References J. Ballato and A. F. Abouraddy, "Feature issue introduction: specialty optical fibers", Opt. Mater. Express 2, 1680-1682 (2012) CrossRef I. Hatakeyama and H. Tsuchiya, "Fusion splices for single-mode optical fibers", IEEE Journal of Quantum Electronics 14, 614-619 (1978) CrossRef K. Inada, O. Watanabe and H. Taya, Splicing of Fibers by the Fusion Method, IEEE Journal on Selected Areas in Communications 4, 706 – 713 (1986) CrossRef L. Xiao, M.S. Demokan, W. Jin, Y. Wang and C. Zhao, Fusion Splicing Photonic Crystal Fibers and Conventional Single-Mode Fibers: Microhole Collapse Effect, J. Lightwave Technol. 25, 3563 – 3574 (2007) CrossRef R.Al-Mahrous, R.Caspary and W.Kowalsky, A thermal splicing method to join silica and fluoride fibers, J. Lightwave Technol. 32 302–308 (2014) CrossRef S. Ertman, A. H. Rodríguez, M. M. Tefelska, M. S. Chychłowski, D. Pysz, R. Buczyński, E. Nowinowski-Kruszelnicki, R. Dąbrowski, and T. R. Woliński, Index guiding photonic liquid crystal fibers for practical applications, J. Lightwave Technol. 30, 1208 - 1214 (2012) CrossRef M. M. Kozak, W. Kowalsky and R. Caspary, Low-loss glue splicing method to join silica and fluoride fibers, Electron. Lett. 41, 21–22, (2005) CrossRef R. Al-Mahrous, R. Caspary, and W. Kowalsky, A Glue Splicing Method to Join Silica and Fluoride Fibers With Low Attenuation, J. Lightwave Technol. 32, 1669-1673 (2014) CrossRef